The use of convective-thermoradiative method of energy supply in the apple snack technology - Malezhyk, Ivan; Dubkovetskiy, Igor; Bandurenko, Halyna; Levkіvska Tetyana; Strelchenko, Ljudmila (Eastern-European Journal of Enterprise Technologies, 2016)
Snacks based on vegetable raw materials are gaining special popularity in the Ukrainian market. As a result of the conducted research, apples of the Champion variety were selected for snacks production. To improve organoleptic indicators of apple snacks, we carried out apples blanching in syrup with the sugar concentration of 40 % and with additional introduction to the solution of citric and ascorbic acids, which significantly improves organoleptic indicators and contributes to product vitaminization. In the process of apples blanching and drying apples, peroxidase inactivation takes place. Its activity per 1 g of the finished product is decreased to 3.4 and 0.36, respectively. Convective-thermoradiative method of energy supply was applied, which intensifies the drying process, contributes to the improvement in quality of the finished product and reduction in energy consumption. In this case, raw material is heated quickly and, due to the use of pulsed mode, is not overheated. It promotes the preservation of original chemical composition of apples, accelerates the drying process by 1.5 times and enables reduction in energy consumption.